Developing an international higher education partnerships between high and low-income countries: two case studies - Teijlingen, Edwin van; Marahatta, Sujan Babu; Simkhada, Padam; McIver, Malcolm; Sharma, Jiwan P. (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
Many people and departments in higher education institutions and hospitals across the globe have objectives that include cross-national partnership working, internationalisation, capacity-building and sharing education and research. We find such commendable ideals at a global level in the Sustainable Development Goals (SDGs) to strategic plans of individual organisations from both low and high-income countries. Using a case-study approach this paper offers insights into some of the key practical issues around global partnership working. We use two case studies of a developing partnership between two separate higher education institutions from the United Kingdom (UK) and one from Nepal. To inform and guide others interested in developing global partnerships we highlight key the reasons for, considerations about, key procedures around the development of such Nepal-UK partnerships and key challenges. Journal of Manmohan Memorial Institute of Health Sciences Vol. 3, No. 1, 2017, page: 94-100